Distal Normograde Intramedullary Pin and Locking Plate Placement in the Canine Humerus: A Cadaveric Study. Issue 7 (9th August 2016) - Pearson, Tim; Glyde, Mark; Hosgood, Giselle; Beierer, Lucas
Abstract : Objective: To identify a repeatable anatomic landmark for pin insertion and to describe the technique for placement of a distal normograde intramedullary (IM) pin of approximately 35% of the IM diameter using this approach combined with a locking compression plate (LCP) on the medial aspect of the canine humerus. Study Design: Ex vivo anatomic study. Sample Population: Canine cadavers (n=10 Greyhounds). Methods: An anatomic landmark for pin insertion was identified based on three‐dimensional reconstructions of previous elbow computed tomography studies and cadaveric dissection of the medial aspect of the humeral condyle. Bilateral distal normograde IM pin and LCP placement were performed and confirmed radiographically and by disarticulation and sagittal sectioning. Results: The anatomic landmark for pin insertion was consistently identified in each specimen using the technique described. Distal normograde insertion of a 3.5 mm IM pin was possible in Greyhound cadaveric humeri at the described location in conjunction with a 3.5 mm LCP with fixed angle, locked screws. A monocortical locking screw was required to avoid interference with the IM pin in 28 of 60 of the 3 proximal screw holes. No pin interference was encountered in any of the distal screw holes. Conclusion: The anatomic landmark and technique described in our study enabled repeatable successful placement of a distal normograde IM pin of approximately 35% of the IM diameter combined with an LCP on the medial aspect of the canine humerus. This technique may be useful for locking plate‐rod fixation of distal humeral diaphyseal fractures.